Formation and Assistance of Disaster Resilient Village In Ngargoyoso Village, Ngargoyoso District, Karanganyar Regency, Central Java - Pipit Wijayanti; Rita Noviani; Anton Sabarno; Aldi Cahyo Saputro; Anastasia Kintan Nimasari; Aufi Nurma Millati; Febi Monica Karina; Hidayat Fauzi; Muchammad Iqbal Dwidya Muzadi; Muhammad Zaki Zamani; Ryan Erry Atmaji; Sheva Adella Novita; Verido Dwiki Herdhianto (Universitas Sebelas Maret, 2020)
The research was carried out in Ngargoyoso Village, Ngargoyoso District, Karanganyar Regency based on the consideration that natural disasters often occur according to landslides. Therefore, an institutional form of Disaster Resilient Village is needed in disaster planning at the village level as a form of increasing disaster preparedness and management. Meanwhile, this research aims to emphasize the village officials, local village youth with the forum Karangtaruna, and the local community. The method of conducting this research is training and mentoring consisting of 6 (six) phases of activities including i) coordination and outreach, ii) FGD (Forum Group Discussion) in a participatory manner by the community, iii) disaster management training, iv) tracing disaster-prone areas, v) assistance in preparing village disaster documents, and vi) evaluating the implementation of activities. The target of the output from the PKM is the formation of the Disaster Resilient Village.